VD_FINDINFO Décision / 2013 / 1035 vom 14. Juni 2013 - VD Tribunal cantonal (2013)
DÉPENS, DOMMAGE PUREMENT ÉCONOMIQUE, PARTICIPATION À LA PROCÉDURE | 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH)